Analisis Kualitas Layanan, Kualitas Interaksi, Dan Fasilitas Layanan Terhadap Kepuasan Masyarakat Desa GIRIPURNO - Ardiana, Miranda Venska; Khalikussabir, Khalikussabir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine and analyze the effect of service quality, interaction quality and service facilities on community satisfaction in Giripuro village. This study uses a verification method with a quantitative approach. and uses a Likert scale as a measurement tool. The sample of this study was selected using a nonprobability sampling technique with a snowball sampling technique with a total of 83 respondents. Primary data were collected through questionnaires distributed via Google Forms. Data testing uses validity, reliability, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination tests with the help of SPSS 26 software. The results of this study indicate that service quality, interaction quality, and service facilities have a simultaneous effect on community satisfaction. Service quality partially affects community satisfaction. Interaction quality partially affects community satisfaction. Service facilities partially affect community satisfaction. Keywords: Service Quality, Interaction Quality, Service Facilities, Community Satisfaction